The Access Pricing Problem with Deregulation: A Note. - Armstrong, M; Vickers, J (Blackwell Publishing, 1998)
This note extends the analysis of M. Armstrong, C. Doyle, and J. Vickers (1996) to the case of retail price deregulation. It is shown that the optimal access price may be above, below, or (in the linear case) equal to marginal cost; that optimal regulation of the margin between the retail price and the access price entails the efficient component pricing rule; and that welfare and entrant profit are higher when the level of the access price, rather than the margin, is regulated.